Myelofibrosis treatment history and future prospects - Amr Ghit (SpringerOpen, 2022)
Abstract Myelofibrosis (MF) is a haematopoietic stem cell tumour caused by the lack of BCR-ABL translocation due to point mutations in Janus kinases (JAKs). In previous years, dealing with MF included several protocols such as traditional drugs that control general symptoms, splenectomy, blood transfusion, and allogeneic haematopoietic stem-cell transplantation (HSCT). Allogeneic HSCT is remaining the only treatment that has the potential to alter MF's progression. However, clinical trials of JAK inhibitors and non-JAK targeted therapies have been increasingly carried out in earlier years. The most prominent JAK inhibitors for the treatment of MF are ruxolitinib, fedratinib, momelotinib, pacritinib, gandotinib, ilginatinib, itacitinib, and lestaurtinib. On the other hand, the non-JAK targeted therapies that showed strong efficacy and safety are alisertib, imetelstat, pembrolizumab, nivolumab, and sotatercept. In this review, we summarized the recent clinical trials carried out on these drugs to understand their efficacy and safety. Also, we talked briefly about allogeneic HSCT as powerful therapy until the present for patients suffering from MF.